110k views
3 votes
What is the missing term?​

What is the missing term?​-example-1
User Dannymac
by
4.7k points

2 Answers

3 votes
Answer: 6x

Reasoning : 2x • 3 = 6x
User Rasmus Puls
by
5.1k points
4 votes

Answer:

Missing term = 6x

Explanation:

We got:

=> 4x by multiplying +4 and x (x * 4 = 4x)

=> 12 by multiplying +4 and +3 (4 * 3 = 12)

=> 2x² by multiplying 2x and x (2x * x = 2x²)

Similarly we will get the "missing term" by multiplying 2x and +3

=> Missing term = 6x, (2x * 3 = 6x)

Hope this helps!

User Trevor Joseph
by
5.2k points